(untitled) - Monthida Sangruangake; Solikhah Solikhah (University of Ostrava, 2021)
Aim: The objective of this study was to translate and evaluate the psychometric properties of the Thai version of the Diabetes Self-Management Scale (T-DSMS). Design: A cross-sectional study. Methods: This study was performed in two phases: 1) a forward-backwards translation of the existing version of the Diabetes Self-Management Scale (DSMS); and 2) evaluation of its psychometric properties using confirmatory factor analysis. Between February to June 2016, a total of 700 type 2 diabetes mellitus (T2DM) patients were recruited from outpatient diabetes clinics of both community and university hospitals in Khon Kaen and Bangkok province Thailand, using a self-administered questionnaire. Results: The results, based on confirmatory factor analysis using Unweighted Least Squares, confirmed the construct validity of the T-DSMS (CFI = 0.985; RMSEA = 0.258; TLI = 0.981; SRMR = 0.040). The T-DSMS contains 13 items across four domains: Diet, Blood, Exercise, and Foot care. Conclusion: We translated and appropriately validated the DSMS in Thai T2DM patients. The T-DSMS was shown to have good psychometric properties, including content validity and criterion validity. The T-DSMS is an adequate instrument with which to assess diabetes self-management in Thai T2DM patients, and can provide valuable insights into the epidemiology of diabetes self-management, and enable evaluation of prevention programs for diabetes self-management in T2DM patients.